Pink Tide 2.0: Kebangkitan Kembali Sayap Kiri Amerika Latin Dan Tantangan Di Masa Depan - Jason Fernando; Abharina Nasution; Daniella Wehelmien Salmun; Jeremy Bryce Lim; Maxi Leinderd (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to explain that left-wing groups have returned to political participation in the Latin American region, which has given birth to the Pink Tide 2.0 phenomenon. The rise of the Pink Tide 2.0 phenomenon began with Mexico in 2018 and Argentina in 2019. This trend continued throughout 2021 and 2022, when many left-wing leaders won elections in Latin America; including Bolivia, Peru, Honduras, Chile, Colombia and Brazil. Elements of the political movement like its predecessor were characterized as